2022
DOI: 10.1093/jee/toac083
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils in Urban Insect Management—A Review

Abstract: The allures of city life have culminated in the rise of urban populations resulting in conditions that promote the establishment of certain insect pests. Globally, the public health significance of these urban insect pests is enormous, ranging from billions of dollars to loss of lives. Most chemical insecticides no longer provide the anticipated level of control, and significant insecticide resistance has been reported. Therefore, there has been a spike in interest for alternatives to conventional insecticides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…For instance, previous studies have shown the repellent effects of essential oils on insects (reviewed in Lee ( 2018)) and also their potential to be used in storage facilities as pest management approaches (Cook et al, 2007b;Nerio et al, 2010;Campolo et al, 2018;Xu et al, 2018;Bandeira et al, 2021), but the use for managing agricultural pests have gained less attention. Essential oils can also be used to manage agricultural pests, but in order to use them in agricultural fields, the essential oils need to be more stable, preventing them from evaporating or biodegrading (Oladipupo et al, 2022). Future studies on C. obstrictus should examine behavioral effects in addition to the effects examined in the present study as exposure to essential oils, as well as treatment residuals, can result in behavioral changes, for example deterring egg laying or acting as antifeedant (Lazarevićet al, 2020;Magierowicz et al, 2020;Stenger et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, previous studies have shown the repellent effects of essential oils on insects (reviewed in Lee ( 2018)) and also their potential to be used in storage facilities as pest management approaches (Cook et al, 2007b;Nerio et al, 2010;Campolo et al, 2018;Xu et al, 2018;Bandeira et al, 2021), but the use for managing agricultural pests have gained less attention. Essential oils can also be used to manage agricultural pests, but in order to use them in agricultural fields, the essential oils need to be more stable, preventing them from evaporating or biodegrading (Oladipupo et al, 2022). Future studies on C. obstrictus should examine behavioral effects in addition to the effects examined in the present study as exposure to essential oils, as well as treatment residuals, can result in behavioral changes, for example deterring egg laying or acting as antifeedant (Lazarevićet al, 2020;Magierowicz et al, 2020;Stenger et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…23 Natural products, particularly essential oils and essential oil constituents, have been a target of intense research over the past decade, in which they have been found to be highly effective as repellents against a variety of pests. 34 Although the repellency of these essential oils and essential oil constituents make them intriguing control alternatives, limited information is available regarding their use against Turkestan cockroaches, North American triatomines, and scorpions. In addition, their main shortcoming is that their effects are typically short lasting: most lose efficacy after 24-48 h. 34 Our study provides evidence that CFAs are highly effective repellents against these pests for at least 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a lower temperature threshold for insect movement imposes a limit on bait efficacy [ 91 ]. The current baits mainly contain relatively nonrepellent, slow-acting compounds [ 90 , 92 , 93 , 94 ]. Most recently, the development of bait technologies for liquid baits with liposomes as carriers of dsRNA has been suggested by several research teams [ 95 , 96 ].…”
Section: Gels Baits For Control Of Ants Cockroaches and Other Urban P...mentioning
confidence: 99%
“…Cockroach pesticide baits—based on locally available natural compounds—have been also explored [ 135 ]. The use of EOs on urban pests has been investigated in the USA [ 94 ], particularly on cockroaches. Oladipupo et al [ 98 ] tested how hydrogels prolong bioavailability of various essential oil components (limonene, carvacrol, and β-thujaplicin,) to control German cockroach ( Blattella germanica ).…”
Section: Gel Formulations With Natural Plant Extracts As Pesticides A...mentioning
confidence: 99%